2022
DOI: 10.1155/2022/9150803
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of the Relevance of Liver, Spleen, and Kidney Dimensions with Body Parameters in Adolescents

Abstract: Objective. Ultrasound is a practical imaging modality for screening and identification of anomalies in the organs. This study used ultrasonography to examine the association between body parameters and dimensions of the normal liver, spleen, and kidney in adolescents based on ultrasound examination results. Methods. A total of 300 junior and senior high school teenagers receiving routine health check-ups in our hospital from January 2020 to January 2021 were included. Their height and weight were measured, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The portal vein diameter and peak flow velocity were measured approximately 1-2 cm in front of the branches emanating from the portal vein trunk. The formula for calculating spleen volume was: (Maximum length × maximum width × maximum thickness × 0.52)[ 25 ]. Severity of ascites were measured as: Grade 1 (mild), < 3 cm depth of ascites; grade 2 (moderate), 3-10 cm; and grade 3 (severe), ≥ 10 cm [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The portal vein diameter and peak flow velocity were measured approximately 1-2 cm in front of the branches emanating from the portal vein trunk. The formula for calculating spleen volume was: (Maximum length × maximum width × maximum thickness × 0.52)[ 25 ]. Severity of ascites were measured as: Grade 1 (mild), < 3 cm depth of ascites; grade 2 (moderate), 3-10 cm; and grade 3 (severe), ≥ 10 cm [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a previous study found associations between waist circumference and spleen volume in a small and selected population (11). Similarly, three studies demonstrated associations of body height, body weight, and BMI with spleen volume in healthy volunteers and adolescents (17)(18)(19). However, in these studies, only indirect methods for measuring body composition were used (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, three studies demonstrated associations of body height, body weight, and BMI with spleen volume in healthy volunteers and adolescents (17)(18)(19). However, in these studies, only indirect methods for measuring body composition were used (17)(18)(19). Similarly, little is known about different obesity marker associations with spleen volume in a general population.…”
Section: Introductionmentioning
confidence: 99%